L'au-delà et sa parousie - Voegelin, Eric (Revue des sciences philosophiques et théologiques, 2009)
In a lecture delivered in 1982, entitled ‘The Beyond and its Parousia’ (translated here for the first time into French), Eric Voegelin (1901-1985) sets out to develop some of the most important concepts in his late philosophy, concepts that this text addresses from the point of view of history and its ‘signification’. In combining a philosophy of consciousness with a philosophy of history, Voegelin opposes all immanentist ideologies inherited from the Enlightenment, which thought it possible to dissolve the tensed, ‘in-between’ structure of human existence. He seeks to restore to consciousness all its original thickness, illuminating it with the help of the Platonic notions of epekeina and parousia of the epekeina. These enable him, he believes, to grasp adequately once more the ‘in-between’ situation that is characteristic of the questioning existence of human beings in the world, as this existence is open erotically to the mystery of being and divine transcendence.